The Relationship between Lifestyle and Hypertension Cases at UPT Cibiru Public Health Center Bandung City - Sutriyawan, Agung; Apriyani, Reni; Miranda, Tenike Gita (Disease Prevention and Public Health Journal, 2021)
Background: Hypertension is one of the non-communicable diseases which is the main cause of death in Indonesia (25.8%). Hypertension is also often called a silent killer because most of the hypertension cases do not cause symptoms. Hypertension is closely related to behavior and lifestyle. Hypertension control is done with behavioral changes, such as conducting adequate physical activity, healthy diet with dietary and quitting smoking. This research aims to determine the relationship between lifestyle, which includes physical activity, diet, and smoking behavior, and hypertension cases. Method: This study used quantitative analytic method with cross sectional research design. The population in this study was all patients who visited and were treated at the public clinic as recorded in the registration report at Cibiru Community Health Center (Puskesmas) in June 2019. The samples were 74 respondents, taken by using purposive sampling technique. The data were analyzed by using the chi square test. Results: The results showed that the lifestyles associated with the hypertension cases were physical activity (p value = 0.022) and smoking behavior (p value = 0.003). Meanwhile, the diet was not related to the incidence of hypertension (p value = 0.326). Conclusion: Based on the research result, it can be concluded that physical activity and smoking behavior were proven to be associated with hypertension, while the diet was not proven related to hypertension. It is suggested that the community health center should maximize the NCD Integrated Guidance Post (Posbindu-PTM) and conduct counseling on the importance of physical activities and the danger of smoking in order to improve the health efforts in the work area of Puskesmas Cibiru.